2015
DOI: 10.1002/2015gl064068
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of heterogeneous ice formation in stratiform clouds over the Amazon Basin

Abstract: Based on 11 months of polarization lidar observations in the Amazon Basin near Manaus, Brazil (2.3∘S, 60∘W), the relationship between temperature and heterogeneous ice formation efficiency in stratiform clouds was evaluated in the cloud top temperature range between −40 and 0∘C. Between −30 and 0∘C, ice‐containing clouds are a factor of 1.5 to 2 more frequent during the dry season. Free‐tropospheric aerosol backscatter profiles revealed a twofold to tenfold increase in aerosol load during the dry season and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…3.1, we ignore a marine contribution of σ m to the particle extinction coefficient in the free troposphere, and therefore a marine contribution to the CCN and INP reservoirs (n CCN , n INP ) in the free troposphere. This is corroborated by our lidar observation at Punta Arenas, Chile, Cape Town, South Africa, aboard the R/V Polarstern, and many Polly lidar sites around the globe (Kanitz et al, 2013;Seifert et al, 2015;Baars et al, 2012Baars et al, , 2016. We conclude from these lidar observations that the marine extinction coefficient σ m is < 1-2 Mm −1 for free-tropospheric heights < 3-5 km, and of the order of 0.01-0.2 Mm −1 for heights > 5 km.…”
Section: Estimation Of N Inp From N 250drysupporting
confidence: 84%
“…3.1, we ignore a marine contribution of σ m to the particle extinction coefficient in the free troposphere, and therefore a marine contribution to the CCN and INP reservoirs (n CCN , n INP ) in the free troposphere. This is corroborated by our lidar observation at Punta Arenas, Chile, Cape Town, South Africa, aboard the R/V Polarstern, and many Polly lidar sites around the globe (Kanitz et al, 2013;Seifert et al, 2015;Baars et al, 2012Baars et al, , 2016. We conclude from these lidar observations that the marine extinction coefficient σ m is < 1-2 Mm −1 for free-tropospheric heights < 3-5 km, and of the order of 0.01-0.2 Mm −1 for heights > 5 km.…”
Section: Estimation Of N Inp From N 250drysupporting
confidence: 84%
“…Ångström exponents were 1.0-1.5, and the observed lidar ratios at 355 and 532 nm were 50-80 sr . Seifert et al (2015) studied the relationship between aerosol properties, temperature, and the efficiency of heterogeneous ice formation in thin stratiform clouds using the data set obtained in Brazil. It was found that the fraction of ice-containing clouds was enhanced by a factor of 1.5 to 2 in the dry compared to the wet season.…”
Section: Southern Hemispherementioning
confidence: 99%
“…Lidars are used since the 1970s to monitor clouds and their evolution, although primarily cirrus and mixed-phase clouds (Platt, 1973(Platt, , 1977Sassen, 1991). Our group also contributed to these observations over the last 25 years (Ansmann et al, 1993(Ansmann et al, , 2005Ansmann et al, 2009;Seifert et al, 2007Seifert et al, , 2010Seifert et al, , 2015Kanitz et al, 2011). Observations are rare in the case of liquid-water clouds because lidars are not appropriate for clouds with typical optical depths of 10 and more.…”
Section: Introductionmentioning
confidence: 99%